Mothers and Queens. Religious Metaphors and Marian Devotion Surrounding Isabel II (1833–1868) in Spain* - Martínez Vilches, David (Journal of religious history, 2021)
This article addresses the use of the parallelisms between the Holy Virgin and Isabel II in the building of the Spanish liberal monarchy's public image (1833–1868). Just like Mary, who was the mother of her child and the mother of Catholics, Isabel II projected her “motherly feelings” beyond her own family to the whole nation through religious metaphors which exhibited her symbolic motherhood. This emotional display of piety, which took place in several Marian shrines of the Spanish geography, was a nationalising and moralising component of the liberal state's attempt to get the crown closer to the citizens. Nevertheless, the symbolic use of religion was a double-edged sword because the queen's sexual behaviour challenged the model of Catholic femininity, so that republicans and Progressives made use of this contradiction between religious discourses and private life to attack the monarchy.